2015
DOI: 10.1063/1.4905141
|View full text |Cite
|
Sign up to set email alerts
|

Novel phases of lithium-aluminum binaries from first-principles structural search

Abstract: Intermetallic Li-Al compounds are on the one hand key materials for light-weight engineering, and on the other hand, they have been proposed for high-capacity electrodes for Li batteries. We determine from first-principles the phase diagram of Li-Al binary crystals using the minima hopping structural prediction method. Beside reproducing the experimentally reported phases (LiAl, Li3Al2, Li9Al4, LiAl3, and Li2Al), we unveil a structural variety larger than expected by discovering six unreported binary phases li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…In particular, we searched for low-energy structures of 9 materials of this family, including SnS 3 , Sn 2 S 5 , SnS 2 , Sn 2 S 3 , SnS, Sn 3 S 2 , Sn 2 S, Sn 5 S 2 , and Sn 3 S, by the minima-hopping method. We then found that Sn 3 S is thermodynamically stable with respect to the decomposition of other related materials and studied this new metallic material by calculations based on density functional theory (DFT). , Our prediction of Sn 3 S aligns well with the recent trend of materials discovery, , revealing that new binary materials with unusual stoichiometries, e.g., NaCl 3 , Na 3 Au 2 , Li 3 Al 2 , Li 9 Al 4 , and LiAl 3 , and Mg 9 Si 5 , , can be found. Second, we provided the community a sizable and reliable data set of 369 new low-energy crystalline structures.…”
Section: Introductionsupporting
confidence: 72%
“…In particular, we searched for low-energy structures of 9 materials of this family, including SnS 3 , Sn 2 S 5 , SnS 2 , Sn 2 S 3 , SnS, Sn 3 S 2 , Sn 2 S, Sn 5 S 2 , and Sn 3 S, by the minima-hopping method. We then found that Sn 3 S is thermodynamically stable with respect to the decomposition of other related materials and studied this new metallic material by calculations based on density functional theory (DFT). , Our prediction of Sn 3 S aligns well with the recent trend of materials discovery, , revealing that new binary materials with unusual stoichiometries, e.g., NaCl 3 , Na 3 Au 2 , Li 3 Al 2 , Li 9 Al 4 , and LiAl 3 , and Mg 9 Si 5 , , can be found. Second, we provided the community a sizable and reliable data set of 369 new low-energy crystalline structures.…”
Section: Introductionsupporting
confidence: 72%
“…We have built the phase diagram for Li-Au, where forty three different stoichiometries starting from pure Li to pure Au were studied. We found that this system has a large number of structures with negative enthalpy, much larger than similar systems which were addressed in parallel, such as LiAl [42] or LiSi [43]. This directly points to a very large number of meta-stable structures as compared with Li-A alloys, where A is an atom with p-valence electrons.…”
Section: Further Discussionmentioning
confidence: 95%
“…41,42 MHM is capable of predicting stable as well as metastable crystal structures at a given pressure, from the sole knowledge of the chemical composition of the system and it has reproduced reported experimental results or found novel structures in many different systems. [49][50][51] After the calculation, the energy per atom for all considered compositions are calculated with respect to the pristine crystals (Li -BCC and Au-FCC). Based on this, the so-called convex hull is constructed, which are all structures with the lowest enthalpy of formation for the specific stoichiometry but that are also more stable with respect to neighbor compositions.…”
Section: Simulated X-ray Diffraction Curve Of LI 5 Au 3 (Space Group mentioning
confidence: 99%